Sodium ion battery, secondary battery, battery pack and energy storage system

By using the stacked first aerogel layer and the second aerogel layer design in the negative electrode sheet of the sodium ion battery, the challenges of the sodium ion battery in terms of high specific capacity, safety and cycle stability are solved, and higher safety and cycle stability are achieved.

CN119542342APending Publication Date: 2025-02-28HUAWEI DIGITAL POWER TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311091749.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-28
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

Existing sodium ion batteries have challenges in high specific capacity, safety and cycle stability, and cannot take into account high specific capacity, high safety and high cycle stability.

Method used

The negative electrode sheet design of the first aerogel layer and the second aerogel layer arranged in a stack are designed, wherein the first aerogel layer contains carbon nanowires and sodium-philic substances, and the second aerogel layer is a sodium-sparse layer. The pores between the two are connected to form a sodium-philic layer and a sodium-sparse layer to avoid the growth of sodium dendrites.

Benefits of technology

It improves the high specific capacity, safety and cycle stability of sodium ion batteries, extends the service life of the battery, inhibits the growth of sodium dendrites, and enhances the safety of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119542342A_ABST
    Figure CN119542342A_ABST
Patent Text Reader

Abstract

The invention provides a sodium ion battery, a secondary battery, a battery pack and an energy storage system. The sodium ion battery comprises a positive pole piece and a negative pole piece, the negative pole piece comprises a first aerogel layer and a second aerogel layer which are arranged in a laminated mode, and at least part of gaps in the second aerogel layer are communicated with at least part of gaps in the first aerogel layer. Therefore, the high specific capacity of the sodium-ion battery is improved, and meanwhile, the safety and the cycling stability of the sodium-ion battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of batteries, and in particular to a sodium ion battery, a secondary battery, a battery pack and an energy storage system. Background Art

[0002] Sodium-ion batteries are expected to alleviate the problem of limited development of energy storage batteries caused by the shortage of lithium resources due to their advantages such as abundant resources and low cost. Negative electrode materials are one of the key components of sodium-ion batteries. The negative electrode materials currently reported for sodium-ion batteries mainly include carbon-based materials, titanium-based materials, organic materials, alloy materials and metallic sodium negative electrodes. Among them, carbon materials have limited sodium storage sites and low reversible specific capacity, which cannot meet the needs of high energy density scenarios. Titanium-based materials have good stability, and the sodium storage potentials of different crystal structures are not the same, but there are problems such as poor electronic conductivity, low first efficiency and low reversible capacity. Organic materials have high structural adjustability, but low electronic conductivity and easy dissolution with electrolytes lead to poor cycle stability. Although alloy materials have high sodium storage specific capacity and low reaction potential, they have poor kinetic performance, huge volume changes in sodium insertion and extraction, and serious cycle performance degradation. The metallic sodium negative electrode has the highest theoretical specific capacity (1166mAh / g) and low electrode potential (-2.71V vs SHE), and is considered to be the most promising high-energy sodium-ion battery negative electrode material. However, its application still faces many challenges, such as safety and life issues caused by sodium dendrite growth and electrode pulverization. Therefore, the current sodium-ion batteries cannot meet the requirements of high specific capacity, high safety and high cycle stability. Summary of the invention

[0003] The present application provides a sodium ion battery, a secondary battery, a battery pack and an energy storage system to improve the safety and cycle stability of the sodium ion battery while improving the high specific capacity of the sodium ion battery.

[0004] In a first aspect, the present application provides a sodium ion battery, the sodium ion battery comprising a positive electrode sheet and a negative electrode sheet, wherein:

[0005] The negative electrode plate comprises a first aerogel layer and a second aerogel layer which are stacked, and the second aerogel layer is arranged on a surface of the first aerogel layer which faces the positive electrode plate;

[0006] The first aerogel layer contains carbon nanowires and a sodium-philic substance, and the first aerogel layer is a porous structure, and a sodium metal layer is formed in the pores of the first aerogel layer;

[0007] The second aerogel layer is a sodium-phobic layer containing carbon nanowires. The second aerogel layer is a porous structure, and at least part of the pores in the second aerogel layer are connected to at least part of the pores in the first aerogel layer.

[0008] The sodium ion battery of the present application, the first aerogel layer in the negative electrode sheet, the carbon nanotubes therein can form the skeleton structure of the first aerogel layer, the sodium-philic substance can be attached to the surface of the carbon nanotubes to attract the deposition of sodium ions, so that the first aerogel layer can form a sodium-philic layer. Since the first aerogel layer is a porous structure, sodium ions can shuttle in the pore structure of the first aerogel layer, and under the action of the sodium-philic substance, a uniform sodium metal layer can be deposited on the surface of the skeleton structure of the first aerogel layer. The second aerogel layer in the negative electrode sheet is a porous structure, at least part of the pores therein are connected to at least part of the pores in the first aerogel layer, so that the sodium ions shuttle between the first aerogel layer and the second aerogel layer. Among them, the carbon nanotubes in the second aerogel layer are themselves sodium-repellent substances, and the second aerogel layer can form a sodium-repellent layer. When sodium ions shuttle between the positive electrode sheet and the negative electrode sheet, the deposition of sodium ions in the second aerogel layer can be avoided under the premise that the second aerogel layer has a sodium-repellent effect. As with lithium, during the deposition process of sodium ions in the second aerogel layer, due to the effect of the sodium-repellent layer, the sodium in the second aerogel layer can be prevented from growing in the first aerogel layer, thereby avoiding the formation of sodium dendrites in the direction from the positive electrode sheet to the negative electrode sheet, thereby inhibiting the growth of sodium dendrites and preventing sodium dendrites from piercing the battery's diaphragm or solid electrolyte layer, thereby improving the safety and cycle performance of the sodium ion battery. In the sodium ion battery, the combination of the first aerogel layer and the second aerogel layer can be used as a negative electrode current collector to achieve conductivity, and the sodium metal layer deposited in the first aerogel layer can be used as a negative electrode material, which has a higher specific capacity and a low electrode potential. Therefore, the sodium ion battery of the present application can obtain higher safety and cycle stability on the basis of having a high specific capacity, thereby extending the service life of the sodium ion battery.

[0009] In an optional implementation, the second aerogel layer has a plurality of through holes, and the plurality of through holes are connected to the pores in the first aerogel layer. By providing the through holes, the shuttling of sodium ions can be facilitated, so that the sodium ions can quickly pass through the first aerogel layer along the through holes, and then the second aerogel layer, or quickly pass through the first aerogel layer from the second aerogel layer into the electrolyte or electrolyte, thereby improving the cycle performance of the sodium ion battery.

[0010] In an optional implementation, the angle between the extension direction of the plurality of through holes and the thickness direction of the second aerogel layer is less than or equal to 35°, preferably less than or equal to 20°. The smaller the angle between the extension direction of the through hole and the thickness direction of the second aerogel layer, the more consistent the extension direction of the through hole is with the thickness direction of the second aerogel layer, and the shorter the time taken by the sodium ions in the shuttling process. In a more preferred implementation, the extension direction of the through hole is consistent with the thickness direction of the second aerogel layer. That is, the extension direction of the through hole is parallel to the direction from the positive electrode sheet to the negative electrode sheet. As a result, the sodium ions have a shorter travel distance during the shuttling process and are more likely to migrate through the second aerogel layer to the void structure of the first aerogel layer.

[0011] In an optional implementation, the through hole has a diameter of 10-100 μm. The through hole has a micrometer-sized diameter, which can facilitate the passage of sodium ions and also facilitate the formation of a porous skeleton of the carbon nanotube aerogel.

[0012] In an optional implementation, the second aerogel layer is a directional freeze-dried aerogel layer. Directed freeze-dried aerogel can form directional extended voids in the aerogel. The second aerogel layer uses a directional freeze-dried aerogel layer, and in the process of preparing the aerogel, the extension direction of the through holes can be consistent with the thickness of the aerogel layer, forming a clustered void structure with consistent direction.

[0013] In an optional implementation, the first aerogel layer is provided with a plurality of first holes, and the angle between the hole depth direction of the plurality of first holes and the thickness direction of the first aerogel layer is greater than or equal to 55°. The setting direction of the first holes in the first aerogel layer is inclined to be perpendicular to the thickness direction of the first aerogel layer. When the angle between the hole depth direction of the first hole and the thickness direction of the first aerogel layer is greater than or equal to 55°, preferably greater than or equal to 70°, especially when the angle between the two is 90°, the sodium ions can migrate rapidly in the first hole along the hole depth direction of the first hole, so as to migrate rapidly in a plane perpendicular to the thickness direction of the first aerogel layer, thereby achieving uniform deposition of the sodium ions in the first aerogel.

[0014] In an optional implementation, the first aerogel layer is a directional freeze-dried aerogel layer. An aerogel layer with a uniform pore size can be obtained by qualitative freeze drying. For example, through-hole directional freeze drying can obtain first holes in the aerogel layer that are substantially perpendicular to the thickness of the first aerogel layer. The extension direction of the plurality of first holes can be the same. For example, the first holes can all extend along the length direction of the aerogel layer, or along the width direction of the aerogel layer.

[0015] In an optional implementation, at least some of the plurality of first holes are connected to the through holes in the second aerogel layer. At least some of the first holes are connected to the through holes, which can facilitate the rapid entry of sodium ions in the first aerogel layer into the second aerogel layer, thereby helping to improve the cycle performance of the sodium ion battery.

[0016] In an optional implementation, the pore size of any first pore among the plurality of first pores is 10-100 μm. The pore size of the first pore is micrometer-sized, which can facilitate the passage of sodium ions and also facilitate the formation of a porous skeleton of the carbon nanotube aerogel.

[0017] In an optional implementation, the sodium-philic substance in the first aerogel layer includes at least one of Ag, Sb, Bi, SnO2, or an oxygen-containing functional group. The sodium-philic substance can be attached to the surface of the carbon nanotube, and when the sodium ions migrate, they can be deposited on the surface of the carbon nanotube to form a sodium metal layer under the action of the sodium-philic substance.

[0018] In an optional implementation, the mass proportion of the sodium-philic substance in the first aerogel layer is 5%-20%. By limiting the content of the sodium-philic substance in the first aerogel layer, the problem of a decrease in the specific capacity of the sodium ion battery caused by excessive sodium-philic substances can be avoided while achieving an effective amount of sodium metal layer deposition.

[0019] In an optional implementation, the carbon nanowire includes at least one of a carbon nanotube or a carbon nanofiber.

[0020] In a second aspect, the present application provides a lithium-ion battery. The lithium-ion battery includes a positive electrode plate and a negative electrode plate, wherein the negative electrode plate includes a first aerogel layer and a second aerogel layer arranged in a stacked manner, and the second aerogel layer is arranged on the surface of the first aerogel layer facing the positive electrode plate. The first aerogel layer contains carbon nanotubes and a lithium-philic substance, and the first aerogel layer is a porous structure, and a lithium metal layer is formed in the pores of the first aerogel layer. The second aerogel layer is a lithium-phobic layer, contains carbon nanotubes, and the second aerogel layer is a porous structure, and at least part of the voids in the second aerogel layer are connected to at least part of the voids in the first aerogel layer.

[0021] The lithium-ion battery of the present application, the first aerogel layer in the negative electrode plate, the carbon nanotubes therein can form the skeleton structure of the first aerogel layer, the lithium-philic substance can be attached to the surface of the carbon nanotubes, used to attract lithium ion deposition, so that the first aerogel layer can form a lithium-philic layer. Since the first aerogel layer is a porous structure, lithium ions can shuttle in the pore structure of the first aerogel layer, and under the action of the lithium-philic substance, a uniform lithium metal layer can be deposited on the surface of the skeleton structure of the first aerogel layer. The second aerogel layer in the negative electrode plate is a porous structure, at least part of the pores therein are connected to at least part of the pores in the first aerogel layer, so that lithium ions shuttle between the first aerogel layer and the second aerogel layer. Among them, the carbon nanotubes in the second aerogel layer are themselves lithium-phobic substances, and the second aerogel layer can form a lithium-phobic layer. When lithium ions shuttle between the positive electrode plate and the negative electrode plate, the second aerogel layer can be prevented from being deposited on the second aerogel layer under the premise that the second aerogel layer has a lithium-phobic effect. During the deposition of lithium, the lithium ions in the second aerogel layer can avoid the growth of lithium in the second aerogel layer in the first aerogel layer due to the effect of the lithium-repelling layer, thereby avoiding the formation of lithium dendrites in the direction from the positive electrode sheet to the negative electrode sheet, thereby inhibiting the growth of lithium dendrites and preventing lithium dendrites from piercing the battery's diaphragm or solid electrolyte layer, thereby improving the safety and cycle performance of the lithium-ion battery. In the lithium-ion battery, the combination of the first aerogel layer and the second aerogel layer can be used as a negative electrode current collector to achieve conductivity, and the lithium metal layer deposited in the first aerogel layer can be used as a negative electrode material, which has a higher specific capacity and a low electrode potential. Therefore, the lithium-ion battery of the present application can obtain higher safety and cycle stability on the basis of having a high specific capacity, thereby extending the service life of the lithium-ion battery.

[0022] In an optional implementation, the second aerogel layer has a plurality of through holes, and the plurality of through holes are connected to the pores in the first aerogel layer.

[0023] In an optional implementation, the angle between the extension direction of the plurality of through holes and the thickness direction of the second aerogel layer is less than or equal to 35°, preferably less than or equal to 20°. In a more preferred implementation, the extension direction of the through holes is consistent with the thickness direction of the second aerogel layer. That is, the extension direction of the through holes is parallel to the direction from the positive electrode sheet to the negative electrode sheet.

[0024] In an optional implementation, the through hole has a diameter of 10-100 μm.

[0025] In an optional implementation, the second aerogel layer is a directional freeze-dried aerogel layer.

[0026] In an optional implementation, the first aerogel layer is provided with a plurality of first holes, and an angle between a hole depth direction of the plurality of first holes and a thickness direction of the first aerogel layer is greater than or equal to 55°.

[0027] In an optional implementation, the first aerogel layer is a directional freeze-dried aerogel layer.

[0028] In an optional implementation, at least some of the plurality of first holes are connected to the through holes in the second aerogel layer.

[0029] In an optional implementation, a pore size of any first hole among the plurality of first holes is 10-100 μm.

[0030] In an optional implementation, the lithium-philic substance in the first aerogel layer includes at least one of Ag, Sb, Bi, SnO2, or an oxygen-containing functional group.

[0031] In an optional implementation, the mass proportion of the lithium-philic substance in the first aerogel layer is 5%-20%.

[0032] In an optional implementation, part or all of the carbon nanotubes in the first aerogel layer may be replaced by carbon nanofibers, and similar effects may be obtained by replacing carbon nanotubes with carbon nanofibers. In addition, part or all of the carbon nanotubes in the second aerogel layer may be replaced by carbon nanofibers, and similar effects may also be obtained.

[0033] In a third aspect, the present application provides a secondary battery, which includes a positive electrode plate and a negative electrode plate; wherein the negative electrode plate includes a first aerogel layer and a second aerogel layer arranged in a stacked manner, and the second aerogel layer is arranged on the surface of the first aerogel layer facing the positive electrode plate; the first aerogel layer contains carbon nanotubes and substances that are pro-active elements; the first aerogel layer is a porous structure, and an active element metal layer is formed in the pores of the first aerogel layer; the second aerogel layer contains carbon nanotubes and does not contain substances that are pro-active elements, the second aerogel layer is a porous structure, and at least part of the gaps in the second aerogel layer are connected to at least part of the gaps in the first aerogel layer; wherein the active element is an element that can shuttle back and forth between the positive electrode plate and the negative electrode plate, including at least one of sodium, lithium, potassium, calcium, magnesium, zinc or aluminum.

[0034] The secondary battery of the present application may be one of a sodium ion battery, a lithium ion battery, a potassium ion battery, a calcium ion battery, a magnesium ion battery, a zinc ion battery or an aluminum ion battery.

[0035] The secondary battery of the present application can obtain similar effects as the sodium ion battery of the first aspect of the present application and the lithium ion battery of the second aspect of the present application, which will not be repeated here. In addition, other features of the negative electrode sheet in the secondary battery of the present application, such as the features of the first aerogel layer and the features of the second aerogel layer, can refer to the features of the negative electrode sheet of the sodium ion battery of the first aspect, which will not be repeated here.

[0036] In a fourth aspect, the present application provides a battery pack comprising a plurality of batteries, wherein the plurality of batteries are connected in series or in parallel; the battery is the sodium ion battery of the first aspect of the present application, or the lithium ion battery of the second aspect of the present application, or the secondary battery of the third aspect of the present application.

[0037] In a fifth aspect, the present application provides an energy storage system, which may include a power converter and at least one battery pack of the present application; the power converter is used to convert the voltage output by the battery pack into power and output it to a power grid or a load, and / or, convert the voltage output by an external power supply into power and output it to the battery pack.

[0038] The technical effects that can be achieved by the fourth to fifth aspects mentioned above can be described with reference to the corresponding effects in the first aspect mentioned above, and will not be repeated here.

[0039] Among them, the data in the above-mentioned possible implementation methods of the present application, such as the angle between the extension direction of the through hole and the thickness direction of the second aerogel layer, the angle between the first hole and the thickness direction of the first aerogel layer, the content of the sodium-philic substance and other data, when measured, the values ​​within the engineering measurement error range should be understood to be within the range defined in the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 A schematic diagram of the structure of a sodium ion battery provided in an embodiment of the present application;

[0041] Figure 2 A schematic diagram of the structure of a negative electrode sheet provided in an embodiment of the present application;

[0042] Figure 3 This is a SEM image of the first aerogel layer according to an embodiment of the present application.

[0043] Reference numerals:

[0044] 11-positive electrode plate; 12-negative electrode plate; 13-diaphragm; 14-electrolyte;

[0045] 121 - first aerogel layer; 1211 - first hole; 122 - second aerogel layer; 1221 - second hole; 123 - carbon nanotube. DETAILED DESCRIPTION

[0046] In order to make the objectives, technical solutions and advantages of the present application clearer, the present application will be further described in detail below in conjunction with the accompanying drawings.

[0047] The terms used in the following embodiments are only for the purpose of describing specific embodiments and are not intended to be limiting of the present application. As used in the specification and appended claims of the present application, the singular expressions "a", "an", "above", "the" and "this" are intended to also include expressions such as "one or more", unless there is a clear contrary indication in the context.

[0048] References to "one embodiment" or "some embodiments" etc. described in this specification mean that a particular feature, structure or characteristic described in conjunction with the embodiment is included in one or more embodiments of the present application. Thus, the phrases "in one embodiment", "in some embodiments", "in some other embodiments", "in some other embodiments", etc. that appear at different places in this specification do not necessarily refer to the same embodiment, but mean "one or more but not all embodiments", unless otherwise specifically emphasized in other ways. The terms "including", "comprising", "having" and their variations all mean "including but not limited to", unless otherwise specifically emphasized in other ways.

[0049] In electronic devices (such as mobile phones, computers, watches and other smart wearable devices) and terminal devices (such as base station equipment, data center equipment, energy storage equipment and electric vehicles), rechargeable batteries, that is, secondary batteries, play the role of energy storage and power supply. In electronic devices, single cells can be directly installed in electronic devices, and single cells can be used to store energy and power electrical components. In terminal equipment, a battery pack formed by connecting multiple single cells in series and parallel can be used to store energy and power electrical components. Existing secondary batteries, such as lithium-ion batteries and sodium-ion batteries, have the problem of forming lithium dendrites or sodium dendrites on the negative electrode sheet during the charge and discharge cycle, thereby reducing the safety performance and cycle performance of the secondary battery. To solve the above problems, an embodiment of the present application provides a secondary battery. The secondary battery of the embodiment of the present application may be, for example, a sodium ion battery, a lithium ion battery, a potassium ion battery, a magnesium ion battery, a calcium ion battery, an aluminum ion battery, and the like.

[0050] The structure of the secondary battery in the embodiment of the present application is described in detail below using a sodium ion battery as an example.

[0051] Figure 1 Figure 1 is a schematic diagram of the structure of a sodium ion battery. Figure 1As shown, the sodium ion battery of the embodiment of the present application includes a positive electrode sheet 11 and a negative electrode sheet 12. A separator 13 may be provided between the positive electrode sheet 11 and the negative electrode sheet 12. The positive electrode sheet 11, the negative electrode sheet 12 and the separator 13 may be packaged in a packaging shell, and the packaging shell may be filled with an electrolyte 14, and the electrolyte 14 infiltrates the positive electrode sheet 11, the negative electrode sheet 12 and the separator 13. During the sodium ion charge and discharge process, the sodium ions migrate between the positive electrode sheet 11 and the negative electrode sheet 12.

[0052] Among them, the positive electrode plate 11 may include a positive electrode collector and a positive electrode coating. The positive electrode collector may be a metal foil, such as an aluminum foil. The positive electrode coating is disposed on at least one side surface of the positive electrode collector. The positive electrode coating may include a positive electrode active material, a binder, a conductive agent, and the like. The positive electrode active material may be selected from transition metal layered oxides, polyanionic compounds, Prussian blue analogs, and the like. The binder may be a commonly used binder for sodium ion batteries such as polyvinylidene fluoride or acrylate-modified polyvinylidene fluoride. The conductive agent may be a commonly used conductive agent for sodium ion batteries such as conductive carbon black. No specific limitation is made on the specific types of the binder and the conductive agent. The structure and composition related to the positive electrode plate may be the relevant composition of a conventional sodium ion battery. No excessive limitation is made on the structure and composition of the positive electrode plate.

[0053] Figure 2 Schematic diagram of the structure of a negative electrode. Figure 2 As shown, the negative electrode sheet 12 of the embodiment of the present application includes a first aerogel layer 121 and a second aerogel layer 122. The first aerogel layer 121 and the second aerogel layer 122 are stacked. The first aerogel layer 121 may be arranged on at least one side surface of the second aerogel layer 122. In the assembled sodium ion battery, the first aerogel layer 121 is arranged toward the positive electrode sheet 11. When the positive electrode sheet 11 is provided on both sides of the negative electrode sheet 12, the second aerogel layer 122 is provided on both side surfaces of the first aerogel layer 121. In order to avoid the first aerogel layer 121 and the second aerogel layer 122 being too thick and affecting the volume energy density of the sodium ion battery, the total thickness of the first aerogel layer 121 and the second aerogel layer 122 is 0.5mm-1.5mm. The thickness of the second aerogel layer 122 may be less than the thickness of the first aerogel layer 121.

[0054] First aerogel layer 121

[0055] Figure 3 This is a SEM image of the first aerogel layer. Figure 2 and Figure 3, the first aerogel layer 121 contains carbon nanotubes 123 and sodium-philic substances. The sodium-philic substances can be uniformly attached to the surface of the carbon nanotubes 123. The first aerogel layer 121 is a porous structure, and its skeleton is a carbon nanotube aerogel. The sodium-philic substance is selected from at least one of Ag, Sb, Bi, SnO2, or oxygen-containing functional groups. In the first aerogel layer 121, the mass proportion of the sodium-philic substance can be, for example, 5%-20%. Exemplarily, the mass proportion of the sodium-philic substance in the first aerogel layer 121 can be, for example, 5%, 8%, 10%, 12%, 14%, 16%, 18%, or 20%. The presence of the sodium-philic substance can cause the first aerogel layer 121 to form a sodium-philic layer, thereby promoting the deposition of sodium ions. Among them, the carbon nanotubes loaded with sodium-philic substances can be prepared by in-situ chemical vapor deposition, hydrothermal reduction, magnetron sputtering and other methods. The first aerogel layer 121 may be a directional freeze-dried aerogel layer. During the preparation process, carbon nanotubes loaded with sodium-philic substances may be directly used as raw materials to prepare the aerogel.

[0056] A sodium metal layer is formed in the pore structure of the first aerogel layer 121. The sodium metal layer may be an active material layer of the negative electrode plate, and is also referred to Figure 1 During the sodium ion charging process, the sodium ions in the positive electrode active material of the positive electrode plate migrate from the positive electrode plate to the negative electrode plate, and the sodium ions obtain electrons in the negative electrode plate and are deposited on the surface of the sodium metal layer. During the discharge process of the sodium ion battery, the sodium atoms in the sodium metal layer lose electrons and become sodium ions, and then migrate to the positive electrode plate. Since the sodium metal layer as a negative electrode active material can have a higher specific capacity and a lower electrode potential relative to the standard potential of hydrogen, the use of the sodium metal layer as a negative electrode active material can make the sodium ion battery have a higher specific capacity and energy density.

[0057] During the charge and discharge cycle of the sodium ion battery, in order to achieve uniform deposition of sodium ions in a plane perpendicular to the thickness direction of the first aerogel layer 121, as Figure 2 As shown, the first aerogel layer 121 may have a first hole 1211. The number of the first holes 1211 may be multiple. The pore size of any first hole among the multiple first holes 1211 may be 10-100 μm. The first hole of this pore size is convenient for electrolyte infiltration and sodium ion passage. The angle between the pore size of the first hole and the pore depth direction 1211 of the first hole and the thickness direction of the first aerogel layer 121 may be greater than or equal to 55°, preferably a direction perpendicular to the thickness of the first aerogel layer. For example, the pore depth direction of the first hole 1211 may be along the length direction of the first aerogel layer, such as Figure 2 The x direction is set, or the depth direction of the first hole 1211 can be along the width direction of the first aerogel layer 121, such as Figure 2 The thickness direction of the first aerogel layer 121 is from the positive electrode sheet to the negative electrode sheet, such as Figure 2It is understandable that, in addition to the first holes, the first aerogel layer 121 may also have holes in other directions.

[0058] The carbon nanotubes in the first aerogel layer can be partially or completely replaced by carbon nanofibers. The carbon nanofibers can form a carbon nanofiber aerogel layer. Sodium-philic substances can also be attached to the surface of the carbon nanofibers. When the first aerogel layer is formed with carbon nanofibers, the carbon nanofibers can form a skeleton structure with a porous structure. The sodium metal layer is deposited on the surface of the carbon nanofibers. The carbon nanotubes or carbon nanofibers can be surface-modified carbon nanotubes or carbon nanofibers. Such as surface-acidified carbon nanotubes or carbon nanofibers.

[0059] Second aerogel layer 122

[0060] Continue to refer to Figure 2 , the second aerogel layer 122 is also a porous structure. The second aerogel layer 122 contains at least one of carbon nanotubes or carbon nanofibers. The carbon nanotubes or carbon nanofibers may be surface-modified carbon nanotubes or carbon nanofibers. Such as surface-acidified carbon nanotubes or carbon nanofibers. The carbon nanotubes and carbon nanofibers may form a porous skeleton structure of the second aerogel layer 122. Among them, the second aerogel layer 122 does not contain sodium-philic substances. The carbon nanotubes and carbon nanofibers themselves are sodium-phobic structures, and thus, the second aerogel layer 122 may be a sodium-phobic layer. When sodium ions pass through the second aerogel layer 122, due to their own sodium-phobic effect, the deposition of sodium ions in the second aerogel layer 122 can be suppressed.

[0061] During the migration process of the sodium ion battery, since the sodium ions need to migrate from the positive electrode plate through the second aerogel layer 122 to the first aerogel layer 121 , at least part of the pores in the first aerogel layer 121 are connected to at least part of the pores in the second aerogel layer 122 .

[0062] In order to facilitate the rapid passage of sodium ions in the second aerogel layer 122, the second aerogel layer 122 has a plurality of second holes 1221, and the second holes 1221 are through holes. The pore size of the through holes is 10-100 μm. Through holes of this pore size are convenient for electrolyte infiltration and the passage of sodium ions. The through holes are connected to the pores in the second aerogel layer 122, and at least part of the through holes are connected to part of the first holes 1211. The angle between the extension direction of the plurality of through holes and the thickness direction of the second aerogel layer 122 may be less than or equal to 35°. In one embodiment, the extension direction of the through holes is consistent with the thickness direction of the second aerogel layer 122. The extension direction of the through holes is arranged along the thickness direction of the second aerogel layer 122, such as Figure 2The z direction in the aerogel layer can reduce the length of the through hole, which is conducive to the rapid passage of sodium ions. The second aerogel layer 122 can also be a directional freeze-dried aerogel layer. The aerogel layer prepared by directional freeze-drying technology can have more consistent and controllable through holes.

[0063] During the charging cycle of the sodium ion battery, the sodium ions can migrate to the first aerogel layer 121 along the through holes in the second aerogel layer 122, and then uniformly deposit in the pore structure of the first aerogel layer 121 along the first hole 1211 in the first aerogel layer 121 to form sodium metal. In this process, since the second aerogel layer 122 is a sodium-phobic layer, the sodium ions will not be deposited in the second aerogel layer 122 when passing through the second aerogel layer 122. The first aerogel layer 121 is a sodium-philic layer, and the sodium ions that migrate from the positive electrode sheet to the first aerogel layer 121 can quickly shuttle in the first aerogel layer 121 and form uniform deposition due to the high affinity between the sodium-philic layer and sodium metal. During the discharge process of the sodium ions, some sodium atoms in the sodium metal layer lose electrons and become sodium ions, and the sodium ions migrate to the positive electrode sheet through the pores in the first aerogel layer 121 and the second aerogel layer 122. During the repeated charge and discharge process of the sodium ion battery, due to the sodium-repellent effect of the second aerogel layer 122, sodium ions are not easily deposited in the second aerogel layer 122, which blocks the growth of sodium dendrites along the thickness direction of the second aerogel layer 122. Therefore, the growth of sodium dendrites can be limited to the first aerogel layer 121, thereby preventing sodium dendrites from piercing the diaphragm and causing a reduction in the safety of the sodium ion battery.

[0064] The sodium ion battery of the present application will be further described in detail below in conjunction with specific embodiments.

[0065] Example 1

[0066] This embodiment is a sodium ion battery, and the specific preparation process is as follows:

[0067] Material preparation:

[0068] Step S11, in-situ loading of silver nanoparticles on carbon nanotubes: silver nitrate, resorcinol and functionalized carbon nanotubes are added to ethanol at the same time, and ultrasonically dispersed for 2 hours to make them evenly mixed and fully reacted. Then the ethanol solution is centrifuged and the supernatant is removed, and the precipitate is obtained to obtain carbon nanotubes loaded with silver nanoparticles, which is recorded as CNT@Ag.

[0069] Step S12, directional freeze drying: the obtained CNT@Ag is added to deionized water, ultrasonically treated for 30 minutes to make it uniformly dispersed, and then directional freeze drying is performed. During directional freeze drying, a temperature gradient from bottom to top is established by bottom cooling and side insulation, so that CNT@Ag generates a first aerogel layer with unidirectional micron-scale pores, a sodium-philic layer. The extension direction of the pores in the sodium-philic layer is perpendicular to the thickness direction of the sodium-philic layer.

[0070] Step S13, directly add the untreated carbon nanotubes into deionized water, ultrasonically treat for 30 minutes to make them uniformly dispersed, and then perform directional freeze drying. During the directional freeze drying, a temperature gradient from bottom to top is established by bottom cooling and side insulation, so that the carbon nanotubes generate a second aerogel layer with unidirectional micron-scale pores, the sodium-repellent layer. The extension direction of the pores in the sodium-repellent layer is the same as the thickness direction of the sodium-repellent layer.

[0071] Battery assembly and performance testing:

[0072] Step S21, button cell assembly: the sodium-philic layer is cut into a sheet A with a thickness of 1 mm and a diameter of 12 mm. The sodium-phobic layer is cut into a sheet B with a thickness of 0.5 mm and a diameter of 12 mm. Sheets A and B are overlapped (sheet B is close to the diaphragm side), and assembled into a CR2032 button cell in an argon glove box with sodium metal as the counter electrode, a glass fiber diaphragm, and 1 M dimethyl ether containing NaPF6 as the electrolyte.

[0073] Step S22, negative electrode sheet preparation: Use the Blue Battery Test System to test the above-mentioned button at 0.1 mA / cm 2 The current density was 0-0.5V, and the charge and discharge cycle was repeated for 3 cycles, and then the discharge was reduced to 0V to complete the negative electrode activation and SEI formation. 2 The aerogel layer is discharged at a current of 1.5 h to deposit metallic sodium on the first aerogel layer, thereby obtaining a negative electrode sheet.

[0074] Step S23, symmetrical battery charge and discharge cycle test: Use the Blue Power Battery Test System to test the button cell, with a charge and discharge current of 10 mA / cm 2 The charge / discharge time is 1.5h, and the cycle test is 1000 times.

[0075] Step S24, deep sodium storage capacity test of negative electrode plate: operate according to the steps in S22 but extend the last step discharge time to 3h, deposit metallic sodium to the first aerogel layer, and obtain a high-capacity negative electrode plate.

[0076] Example 2

[0077] The material preparation process is the same as that in Example 1.

[0078] Battery assembly and performance testing:

[0079] Step S21, button cell assembly: the sodium-philic layer is cut into a sheet A with a thickness of 0.5 mm and a diameter of 12 mm, and the sodium-phobic layer is cut into a sheet B with a thickness of 0.5 mm and a diameter of 12 mm. The sheet A is overlapped with the sheet B (sheet B is close to the diaphragm side), and assembled into a CR2032 button cell in an argon glove box with sodium metal as the counter electrode, a glass fiber diaphragm, and 1M dimethyl ether containing NaPF6 as the electrolyte.

[0080] Step S22, negative electrode sheet preparation: Use the Blue Battery Test System to test the above-mentioned button at 0.1 mA / cm 2 The current density was 0-0.5V, and the charge and discharge cycle was repeated for 3 cycles, and then the discharge was reduced to 0V to complete the negative electrode activation and SEI formation. 2 The aerogel layer is discharged with a current of 1 h to deposit metallic sodium on the first aerogel layer, thereby obtaining a negative electrode sheet.

[0081] Step S23, symmetrical battery charge and discharge cycle test: Use the Blue Power Battery Test System to test the button cell, with a charge and discharge current of 10 mA / cm 2 The charge / discharge time is 1h, and the cycle test is 1000 times.

[0082] Step S24, negative electrode deep sodium storage capacity test: follow the steps in S22 but extend the last step discharge time to 2h, deposit metallic sodium on the first aerogel layer to obtain a high-capacity negative electrode plate.

[0083] Comparative Example 1

[0084] The material preparation process is the same as that in Example 1.

[0085] Battery assembly and performance testing:

[0086] Step S21, button cell assembly: cut the sodium-philic layer into a sheet A with a thickness of 1 mm and a diameter of 12 mm, and assemble it into a CR2032 button cell in an argon glove box with the counter electrode sodium metal, a glass fiber separator, and 1 M dimethyl ether containing NaPF6 as an electrolyte.

[0087] Step S22, negative electrode sheet preparation: Use the Blue Battery Test System to test the above-mentioned button at 0.1 mA / cm 2 The current density was 0-0.5V, and the charge and discharge cycle was repeated for 3 cycles, and then the discharge was reduced to 0V to complete the negative electrode activation and SEI formation. 2 The aerogel layer is discharged with a current of 1.5 h to deposit metallic sodium on the aerogel layer, thereby obtaining a negative electrode sheet.

[0088] Step S23, symmetrical battery charge and discharge cycle test: Use the Blue Power Battery Test System to test the button cell, with a charge and discharge current of 10 mA / cm 2The charge / discharge time is 1.5h, and the cycle test is 500 times.

[0089] Step S24, negative electrode deep sodium storage capacity test: follow the steps in step S22 but extend the last step discharge time to 3h, deposit metallic sodium into the aerogel layer to obtain a high-capacity composite negative electrode plate.

[0090] Comparative Example 2

[0091] Battery assembly and performance testing:

[0092] Button cell assembly: Sodium metal, sodium metal counter electrode, glass fiber separator, and 1 M dimethyl ether containing NaPF6 as electrolyte were assembled into a CR2032 button cell in an argon glove box.

[0093] Symmetrical battery charge and discharge cycle test: Use the Blue Power battery test system to test the button battery, the charge and discharge current is 5mA / cm 2 The charge / discharge time is 1h, and the cycle test is 100 times.

[0094] Metal anode sodium deposition capacity test: 5mA / cm 2 The current is discharged for 1 hour to deposit metallic sodium on the opposite electrode.

[0095] The deposition capacity, deposition overpotential, cycle capacity and cycle overpotential of each embodiment and comparative example after several cycles are tested. The number of charge and discharge cycles and the test results are listed in Table 1.

[0096] Deposition capacity: Deposition capacity mAh / cm 2 = set current density mA / cm 2 × Set the charging time in h.

[0097] Deposition overpotential: The absolute value of the measured charging platform voltage.

[0098] Cycle capacity: Cycle capacity mAh / cm 2 = set current density mA / cm 2 × Set the charging time per lap in h.

[0099] Cycle overpotential: The absolute value of the charging platform voltage at the 1000th cycle measured.

[0100] Table 1

[0101]

[0102] It can be seen from the data in Table 1 that after 1000 cycles, the present embodiment 1 and embodiment 2 still have a relatively high level compared with the deposition capacity. The cycle overpotential has not been greatly improved, and is below 50mV, while the sodium ion batteries of comparative examples 1 and 2 have a significantly improved cycle overpotential. This shows that the sodium ion batteries of the present embodiment have excellent cycle stability.

[0103] The charge-discharge overpotential of the composite negative electrode in Example 1 after 1000 cycles is only 20 mV, and the cycle capacity after 1000 cycles can reach 15 mAh / cm 2 , indicating that the composite electrode of Example 1 has a high deposition stripping capacity and excellent stability under high current charge and discharge cycles. The deposition capacity of the composite negative electrode can reach 30 mAh / cm 2 , indicating that the composite electrode of Example 1 can have a deep sodium storage capacity.

[0104] The composite negative electrode in Example 2 has a charge-discharge overpotential of 36 mV after 1000 cycles, and a cycle capacity of 10 mAh / cm after 1000 cycles. 2 Similarly, it shows that the composite negative electrode has a high deposition stripping capacity and excellent stability under high current cycling; the deep sodium storage capacity of the composite negative electrode can reach 20mAh / cm 2 .

[0105] The composite negative electrode in Example 1 has a deep sodium storage capacity of up to 30 mAh / cm 2 However, its charge and discharge overpotential after 500 cycles is 110 mV, indicating that the composite negative electrode of Comparative Example 1 has poor stability under high current cycling.

[0106] The composite negative electrode in Example 2 has a charge-discharge overpotential of 171 mV after 100 cycles of deposition and peeling, indicating that its stability is poor. And after 100 cycles, its cycle capacity has dropped to 5 mAh / cm 2 .

[0107] The above are only specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any technician familiar with the technical field can easily think of changes or substitutions within the technical scope disclosed in the present application, which should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.

Claims

1. A sodium ion battery, characterized in that: It includes a positive electrode sheet and a negative electrode sheet, wherein: The negative electrode plate comprises a first aerogel layer and a second aerogel layer which are stacked, and the second aerogel layer is arranged on a surface of the first aerogel layer which faces the positive electrode plate; The first aerogel layer contains carbon nanowires and a sodium-philic substance, and the first aerogel layer is a porous structure, and a sodium metal layer is formed in the pores of the first aerogel layer; The second aerogel layer contains carbon nanowires, the second aerogel layer is a porous structure, and at least part of the pores in the second aerogel layer are connected with at least part of the pores in the first aerogel layer.

2. The sodium ion battery according to claim 1, characterized in that The second aerogel layer has a plurality of through holes, and the plurality of through holes are connected to the pores in the first aerogel layer.

3. The sodium ion battery according to claim 2, characterized in that: An angle between an extension direction of the plurality of through holes and a thickness direction of the second aerogel layer is less than or equal to 35°.

4. The sodium ion battery according to claim 2 or 3, characterized in that: The through hole has a diameter of 10-100 μm.

5. The sodium ion battery according to any one of claims 1 to 4, characterized in that: The second aerogel layer is a directional freeze-dried aerogel layer.

6. The sodium ion battery according to any one of claims 1 to 5, characterized in that: The first aerogel layer is provided with a plurality of first holes, and an angle between a hole depth direction of the plurality of first holes and a thickness direction of the first aerogel layer is greater than or equal to 55°.

7. The sodium ion battery according to claim 6, characterized in that: The pore size of any first pore among the plurality of first pores is 10-100 μm.

8. The sodium ion battery according to claim 6 or 7, characterized in that: At least some of the plurality of first holes are communicated with the through holes in the second aerogel layer.

9. The sodium ion battery according to any one of claims 1 to 8, characterized in that: The sodium-philic substance includes at least one of Ag, Sb, Bi, SnO2, or an oxygen-containing functional group.

10. The sodium ion battery according to any one of claims 1 to 9, characterized in that: The mass proportion of the sodium-philic substance in the first aerogel layer is 5%-20%.

11. The sodium ion battery according to any one of claims 1 to 6, characterized in that: The carbon nanowire is selected from at least one of carbon nanotubes and carbon nanofibers.

12. A secondary battery, characterized in that: It includes a positive electrode sheet and a negative electrode sheet; wherein, The negative electrode plate comprises a first aerogel layer and a second aerogel layer which are stacked, and the second aerogel layer is arranged on a surface of the first aerogel layer which faces the positive electrode plate; The first aerogel layer contains carbon nanotubes and substances that are pro-active elements, the first aerogel layer is a porous structure, and an active element metal layer is formed in the pores of the first aerogel layer; The second aerogel layer contains carbon nanotubes and does not contain substances that are pro-active elements, the second aerogel layer is a porous structure, and at least part of the gaps in the second aerogel layer are connected to at least part of the gaps in the first aerogel layer; The active element is an element that can shuttle back and forth between the positive electrode plate and the negative electrode plate, including at least one of sodium, lithium, potassium, calcium, magnesium, zinc or aluminum.

13. A battery pack, characterized in that: The battery pack comprises a plurality of batteries, and the plurality of batteries are connected in series or in parallel; the battery is a sodium ion battery as described in any one of claims 1 to 11, or a secondary battery as described in claim 12.

14. An energy storage system, characterized in that: The energy storage system includes a power converter and at least one battery pack as described in claim 13; the power converter is used to convert the voltage output by the battery pack into power and output it to a power grid or a load, and / or to convert the voltage output by an external power supply into power and output it to the battery pack.